Alcohol Abuse and Dependence Symptoms: A Multidimensional Model of Common and Specific Etiology - Simons, Jeffrey S. (2009)
This study tested a theoretical model hypothesizing differential pathways from five predictors to alcohol abuse and dependence symptoms. The participants were college students (N= 2,270) surveyed on two occasions in a 6-month prospective design. Social norms, perceived utility of alcohol use, and family history of alcohol problems were indirectly associated with Time 2 (T2) abuse and dependence symptoms through influencing level of alcohol consumption. Poor behavioral control had a direct effect on alcohol abuse but not dependence symptoms at T2, whereas affective lability exhibited a direct prospective effect on alcohol dependence but not abuse symptoms. A multigroup analysis showed that high levels of poor control increased the strength of paths from both consumption level and affective lability to abuse symptoms. Implications for prevention of alcohol problems among college students are discussed.